Fisiopatologia del sistema digestivo y necesidades nutricionales del cuy (cavia porcellus) (2020)
The following degree monograph was carried out with the objective of describing the digestive pathophysiology and nutritional needs of guinea pig (Cavia porcellus), in order to determine the main digestive pathologies (salmonella, parasitosis, etc.).